Looking into the rear-view mirror: Lessons from Japan for the Eurozone and the U.S? - Pierre L. Siklos (Elsevier, 2021)
This paper reconsiders the narratives surrounding Japan's economic performance since the 1980s in relation to the experiences of the U.S. and the Eurozone. There are important differences between these three economies and some striking parallels. It is found that the poor reputation of the Bank of Japan (BoJ) is, at times, underserved. To be sure, there were periods of excessive tightness in policy, but the same is true for the other two economies considered. Indeed, the BoJ has been more credible than the other two central banks considered at various times over the past three decades.In addition, a look back at BoJ over the decades does not provide much support the hypothesis that a significant policy break translates into economic success. Instead, smaller changes are just as likely to lead to a tipping point with significant consequences. Indeed, some narrative-based significant regime shifts do not show in the data.